Acute Motor Axonal Neuropathy (Aman) With Motor Conduction Blocks In Childhood; Case Report - Yildirim, Serhan (Iran J Child Neurol, 2016)
Objective Acute motor axonal neuropathy (AMAN), characterized with decreased compound muscle action potentials (CMAP) and absence of demyelinating findings in electrophysiological studies, is a subtype of Guillain-Barre Syndrome (GBS). A 4 yr-old male patient presented with ascending weakness, dysarthria and dysphagia to İstanbul Dr. Lütfi Kırdar Kartal Training and Research Hospital Neurology outpatient for three days to in 2012. Dysphonia, restricted eye movements, flaccid tetraplegia and areflexia were found in neurological examination. There were motor conduction blocks in all peripheral nerves in electrophysiological studies.According to these findings the patient was diagnosed as Acute Inflammatory Demyelinating Polyradiculoneuropathy (AIDP). Reduction of CMAP amplitudes in posterior tibial nerve, absence of CMAPs in median, ulnar and peroneal nerves and loss of motor conduction blocks were found in following electrophysiological studies. According to these findings, patient was diagnosed as AMAN. Motor conduction blocks may appear in early stage of AMAN and they disappear in later examinations. That’s why electrophysiological studies must be repeated in patients with GBS.